Performance Panel Surya Saat Gerhana Matahari Cincin Pada Tanggal 26 Desember 2019 Di Kecamatan Larangan Kabupaten Brebes - Su Dar mono; Joko Waluyo; Wahyu Wilopo (Universitas Muhammadiyah Purwokerto, 2021)
The purpose of this research is to know the performance of PV technology by using PV Solartracker on the eclipse Ring on 26 December 2019 by varying the net and dirty PV using themethod of Penyesuian sun position In one year. The study simulates using a solar panel capacity of3 watts and 6 volts with a lithium battery load capacity of 4000 mAh, the direction of the solarpanel is in the south with a tilt angle 230 in December each Stepnya solar tracker This 3- hourchanging angle 450, 900 and 1150 This research began from the hour 07:00 to 15:00 hours. Theaverage power of the solar power plant was received by 1.08 Watts, 4.24 Volt, 0.25 amper and netPV capacity of 2108 mAh, while with an average power of 0.83 watts, 4.36 volts, 0.19 Amper andgross PV capacity of 1524 mAh.